Theme, genre and structure of ‘Every good man is free’. Evidence for authenticity of Philo's authorship (Circe de clásicos y modernos, 2024)
This article is an introduction to ‘Every good man is free’, which is little known and only partially quoted in Philonian studies. We begin by summarizing the subject of the treatise and make some considerations about its literary genre. When we briefly develop the structure of the work, we offer at the same time a summary of its contents part by part. We dedicate a subtitle to the Essene community, because it is the most quoted fragment and comprises an important portion of the treatise (§§73-91). Finally, in order to elucidate whether the work is authored by Philo we mark differences and similarities with the theological position of the Alexandrian in other treatises and list certain topics and rhetorical figures that appear in our text.
Keywords: Philo; Probus; Essenes; Stoicism